The first Industrial Hygiene Congresses in Milan - Porro, Alessandro (La Medicina del Lavoro, 2019)
The first Congress of the Italian Association of Industrial Hygienists was held in 1977. Nevertheless, at the end of the 19th century some issues concerning industrial hygiene had been discussed during the 3rd International Congress on Accidents and Social Insurance (Milan, October 1-6, 1894). A year later, the Milanese trade Unions held another Congress on this theme. In 1902 Leopoldo Sconfietti, an engineer, proposed a new system of air conditioning to be used in textile factories. After the EXPO 1906 in Milan, a museum devoted to Industrial Hygiene was opened in the city, but unfortunately it is now lost. Soon after the opening in 1910 of the Milanese “Clinica del Lavoro”, the oldest Occupational Health Institute in the world, an International technical Congress devoted to Industrial Hygiene was held in Milan in May 1912, when the discipline became autonomous from Occupational Medicine and Social Insurance.